Digital Transformation in Education: A Comprehensive Bibliometric Analysis, Government Initiatives and Challenges - Dahiya, Priya; Kishnani, Somya; Kishnani, Shivani; Dahiya, Rinki; Deepika (Indian Journal of Educational Technology, 2025)
The escalating significance of digital transformation in education signifies a paradigm shift in learning delivery, driven by technological advancements like AI, virtual reality, and data analytics. It aims to enhance accessibility, personalise learning, and foster collaborative experiences. This research explores the evolution of digital transformation research in education, tracing its trajectory from basic tools to comprehensive restructuring. A bibliometric analysis reveals a surge in research publications post 2019, influenced by seminal articles and the COVID-19 pandemic. Citation analysis highlights impactful papers, emphasising the pandemic’s profound impact on digital education. Keyword network maps and cluster analysis unveil research trends, while initiatives in India exemplify government efforts in digital education transformation, ensuring inclusivity and accessibility. Despite digital transformation’s positive impact on education, strategic high-level challenges persist. Resistance to change impedes the adoption of new methods, necessitating effective leadership, pilot projects, and orientation programs. Technology infrastructure challenges, including glitches and data security concerns, underscore the need for investments in stable technologies. Compatibility issues with existing systems and the lack of a clear strategy pose hurdles, emphasising robust planning and phased implementation. Additionally, inferior technology skills and inequality in access necessitate training programs and measures to address socio-economic disparities for successful digital transformation in education.